Eastern Region Transport Survey Volume VI Air Transport, Inland Water Transport and Other Modes Planning Commission Government of India - Planning Commission (Planning Commission, 1967)
The Eastern Region Transport Survey was initiated jointly by the Planning Commission and the Ministries of Railways, Transport and Shipping and Civil Aviation and Tourism, through the Joint Technical Group for Transport Planning.
Regional Transport Survey Unit, Planning Commission, Government of India